National-survey for evaluation of the best screening method of late fetal growth restriction in low risk pregnancy: A prospective study. (September 2019) - Policiano, Catarina; Reis-de-Carvalho, Catarina; Clode, Nuno; Mendes Graça, Luís
Abstract: Objective: To compare knowledge and practices surrounding third trimester screening of fetal growth restriction (FGR) in low risk pregnancies among Portuguese Gynecologists/Obstetricians (GOs) and General Practitioners (GPs). Primary outcome was to compare the proportion of GOs that consider the need of a third trimester ultrasound (estimation of fetal weight) for screening of FGR in low risk pregnancies and the best time to perform it with the corresponding proportion of GPs. Study design: We have conducted a prospective, observational cohort study based on application of surveys to GOs and GPs. Questionnaires were sent by e-mail to physicians and they filled them online. A second reminder e-mail was sent 7 days later. Recruitment was also done personally at scientific meetings. A total of 573 surveys were available for analysis, 298 corresponded to GOs and 275 to GPs. We used χ 2 test to compare dichotomous variables and Kruskal-Wallis test for the comparison of ordinal variables. P values <0.05 were considered statistically significant. Results: The vast majority of GOs and GPs (93%) considered that third trimester ultrasound is useful and needed for surveillance of low risk pregnancy. A higher proportion of GOs (38%) selected 35th–37th weeks as the best time to perform the ultrasound compared to GPs (10%) (p < 0.001). GOs (51%) consider that symphysis-fundus distance is a measurement with moderate accuracy for screening of FGR while GPs (61%) attribute a low accuracy (p < 0.001). Fifty percent (50%) of GOs consider that performing a third trimester ultrasound will have no impact on cesarean delivery rate for fetal distress, while 41% of GPs consider that routine ultrasound will contribute to increase this rate (p < 0.001). The majority of GPs (52%) consider that routine ultrasound will contribute to diminish the admission rate to neonatal intensive care unit while GOs revealed a dichotomy with 43% of respondents reporting that it will diminish the rate and 40% that it will have no impact. Conclusion: Varied opinions among the clinicians included in our sample reflect the controversy that remains on the best screening of FGR in low risk pregnancies.